International Polar Week as an educational activity to boost science–educational links: Portugal as a case study. (19th February 2019) - Xavier, José C.; Azinhaga, Patrícia Fialho; Seco, José; Fugmann, Gerlis
Abstract: International Polar Week is an educational activity that has been carried out since the International Polar Year 2007–2008 (known then as International Polar Days). This event, which brings together educators and polar scientists to promote polar science, is generally organised by the Association of Polar Early Career Scientists and Polar Educators International. Here we provide an overview of how International Polar Week started, and describe its implementation in Portugal, a "non-polar" country. We quantify the activities carried out during International Polar Weeks in Portugal between 2012 and 2017, which involved >96, 000 students, >200 schools, >1900 educators and 100 polar scientists, with talks and Skype calls by polar scientists being the most frequent activities. Portugal's International Polar Weeks have involved students, educators and polar scientists from 18 other countries, in particular from the United Kingdom and Brazil. We conclude by providing recommendations to other countries wanting to implement International Polar Weeks.